THE INFLUENCE OF ACCOUNTS RECEIVABLE TURNOVER AND CASH TURNOVER ON LIQUIDITY AT CV KURNIA JAYA MANDIRI PEKANBARU - Fadrul Fadrul; Amelia Surya (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
The purpose of this research is to figure out the influence of receivable turnover and cash turnover on Liquidity at CV Kurnia Jaya Mandiri Pekanbaru. The method used in this research are descriptive and quantitative methods. The result of this research indicates that the independent variables (receivable turnover and cash turnover) have no significant effect on the dependent variable (liquidity) in CV Kurnia Jaya Mandiri Pekanbaru. This research suggest that the company need to always control the flow of cash in and cash out so the efficiency of cash utilization can be increase.